CORRELATION BETWEEN POINT-OF-CARE AND LABORATORY-BASED AUTOMATED BLOOD GLUCOSE TESTING (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetes mellitus is a growing global health concern, with rising prevalence particularly in low- and middle-income countries. Accurate blood glucose estimation is essential for diagnosis, monitoring, and prevention of complications. While glucometers provide rapid, convenient results at the point of care, laboratory autoanalyzer are considered more reliable. This study aimed to compare the accuracy and correlation between these two methods. Methodology: A comparative study was conducted on 150 patients above 18 years, including both diabetic and non-diabetic individuals. Capillary blood glucose was measured using a glucometer via finger prick, while venous blood samples were analysed using a laboratory autoanalyzer. Statistical analysis done by paired t-test. Result: The mean blood glucose level obtained from the glucometer was approximately 8.49 mg/dL higher than that of the autoanalyzer. A strong positive correlation was observed (r = 0.959), indicating that both methods follow a similar trend. However, the paired t-test (t = 4.68, p < 0.001) showed a statistically significant difference. Discussion: The findings indicate that glucometers tend to overestimate glucose levels, consistent with previous studies. This discrepancy may arise due to operational errors such as expired strips, improper sample handling, or device calibration issues. Such inaccuracies can lead to inappropriate clinical decisions, especially in critical glycemic conditions. Conclusion: Although glucometers are useful for routine monitoring and point-of-care testing, they are not fully interchangeable with laboratory methods due to significant bias. Laboratory autoanalyzers remain the gold standard for accurate glucose estimation.